Literacy entrepreneurship exploration: Students' perceptions of business opportunities in language and literature - Ulya, Chafit; Suwandi , Sarwiji; Wardani , Nugraheni Eko; Setiyoningsih, Titi; Havyarimana , Célestin (BAHASTRA, 2024)
Literacy entrepreneurship is a field of entrepreneurship that focuses on developing language and literature-based products and services to strengthen literacy culture in society. The role of higher education is very important in fostering the entrepreneurial spirit of literacy. Research shows that many students still face challenges in developing literacy-based businesses, such as a lack of knowledge about business management, unsupportive attitudes, and inadequate practical skills. Therefore, it is important to explore the level of entrepreneurial literacy knowledge, attitudes and skills among college students in order to design effective educational programs. Entrepreneurship education in higher education does not only focus on opening a business, but also on forming character, mindset and entrepreneurial behavior. This research aims to fill this gap by analyzing the level of knowledge, attitudes and literacy entrepreneurial skills of students, as well as providing recommendations for developing a more effective and comprehensive literacy entrepreneurship education curriculum. It is hoped that the research results can be used by higher education institutions to design programs that are more suited to student needs and support the development of literacy entrepreneurship education programs